Family Rhythms: Re-visioning family change in Ireland using qualitative archived data from Growing Up in Ireland and Life Histories and Social Change. Issue 2 (August 2017) - Geraghty, Ruth; Gray, Jane
The Family Rhythms project examined the Irish experience of family life over an extended period of time, in which we traced evolving relationships and practices against a backdrop of immense social, cultural and economic change, from the early years of the Irish state to the present day. We combined qualitative data from Growing Up in Ireland (GUI), with Life Histories and Social Change (LHSC) to construct a longitudinal, qualitative database with a distinct focus on family relationships. Family Rhythms demonstrated the potential for bringing data from two major qualitative studies into dialogue to develop new insights into the motives, feelings and rationalities behind Irish people's family practices and experiences in changing social contexts. Combining the data from two unrelated studies presented methodological challenges, namely how to consolidate these data and how to compare the retrospective life story data in LHSC with the prospective data in GUI. To overcome this, we worked 'forwards' and 'backwards' across the two collections to specify patterns of continuity and change in key dimensions of family relationships. The strengths of this dynamic approach were that we could examine family relationships across an extended timeframe and from different generational standpoints.